Zu einer Ästhetik der Schwelle. Philosophische Reflexionen am Beispiel vom Musiktheater im Revier (Itinera, 2023)
The essay develops an aesthetic of the threshold from an analysis of the artistic collaboration between Werner Ruhnau and Yves Klein for the realisation of the Musiktheater im Revier in Gelsenkirchen. The threshold is a figure of thought that stands for the artistic choice to create zones of interaction between work and spectator, in which exchanges of roles and production of meaning take place. The aesthetics of the threshold in Ruhnau manifests itself through the architectural design of playful theatrical spaces in which the theatre audience can stage new identities. In Klein, the threshold becomes a meditative space, through which the subject trains his faculties of feeling and making sense. In the “Verfransung” (Adorno) between the strategies of Ruhnau and Klein, the theatre becomes the threshold for an interaction between public space and sensibility.
Keywords: Threshold, Play, Sensibility, Verfransung.